Incidence and Identification of Klebsiella planticola in Clinical Isolates with Emphasis on Newborns - Westbrook, Glennis L. (American Society for Microbiology, 2000)
Studies conducted in France and Germany suggest that up to 19% of clinically identified Klebsiella sp. are actually Klebsiella planticola, an environmental species that has been attributed to two cases of septicemia, with a rare isolate of Klebsiella terrigena (0.4%) being identified. A 1-year survey of newborns on a neonatal ward, also conducted in Germany, reported that 72% of Klebsiella sp. were Klebsiella oxytoca and 8.7% were K. planticola. The tests necessary to identify these species are not found in most clinical identification schemes or in the database matrices of most commercial identification products. To determine the incidence of unrecognized K. planticola among the Klebsiella sp. isolates in our collection, we used the battery of seven supplemental tests amended from the work of Monnet and Freney to test 352 stock isolates and 84 fresh clinical isolates from four local hospitals. After testing 436 strains of Klebsiella, only one strain was identified as a possible K. planticola and none was identified as K. terrigena. We tested an additional 43 stock strains of K. oxytoca isolated from newborns by using eight biochemical tests and found one additional strain of K. planticola. The occurrence of K. planticola in our collection is far less frequent than that observed in other countries.